Upaya Prevensi Orang Tua Mencegah Kenakalan Remaja - Danis Feny Suwella; Sri Mugianti; Triana Setijaningsih; Suprajitno Suprajitno (Journal of Ners and Midwifery, 2016)
The research purpose was to describe the preventive efforts of parents in preventing juvenile delinquency. The research design was descriptive and the data was collected with a questionnaire. Thepopulation was 251 parents. The sample was 38 respondents taken by using quota sampling technique. The data collection was conducted in March-April 2015. The survey results revealed that the preventiveefforts of the parents in preventing juvenile delinquency by 84.2% (32 people) in a good category, 13.2% (5 people) in a sufficient category and 2.6% (1 person) in a bad category. Preventive efforts inbad category were in a small percentage, but it would have a negative impact if not being handled. Based on the results of the research, it is expected that school provides socialization to the parentsabout the prevention of juvenile delinquency and make a good cooperation in preventing juvenile delinquency.